Stability for a sliding mode fuzzy control applied to a pneumatic parallel robot - Pablo J. Prieto; Nohe R. Cazarez Castro; Dianelis García; Selene L. Cárdenas Maciel (Revista Iberoamericana de Automática e Informática Industrial RIAI)
In this paper is reported a Mamdani type fuzzy controller based on sliding mode techniques applied to the regulation of a 2 DOF pneumatic parallel robot. Is is proved that the system is stable in Lyapunov sense, and numerical and experimental results are reported. Moreover, the designed controller can be applied to tracking control if speed and acceleration from the system are feedbacked. Also are reported satisfactory experimental results for the tracking case.